Nasal cavity coated drug-loaded stent and preparation method thereof
By adopting a coated drug-loading stent on the nasal drug-loading stent and using the drug coating of non-degradable materials and polymer carriers, the problems of unstable drug release and insufficient wound contact in the prior art are solved, and long-term stability is achieved Support and tissue regeneration guidance.
Patent Information
- Application Number
- CN202411384653.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-14
AI Technical Summary
Existing nasal drug-loading stents are difficult to ensure full wound contact and high drug loading after large wound surgery, resulting in poor anti-inflammatory and anti-adhesion effects, and unstable drug release, affecting tissue regeneration.
Designed with coated drug-loading stents, including bare stents and coatings made of non-degradable materials, the drug coating is formed of polymer carriers, coated by ultrasonic spraying process to ensure long and stable drug release cycles and is applied on drug coating. A tissue regeneration guide layer is provided on the layer.
It achieved long-term and stable support after large wound surgery, and the drug release was stable for 2-4 months, enhancing anti-inflammatory and anti-adhesion effects, and guiding tissue regeneration, improving the wound repair effect.
Smart Images

Figure CN119424773A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nasal stents, and in particular to a nasal membrane-covered drug-loaded stent and a preparation method thereof. Background Art
[0002] Chronic rhinosinusitis (CRS) is a common disease in otolaryngology and head and neck surgery. It is a chronic inflammatory disease of the sinus mucosa, affecting 12%-15% of the world's population. Patients mainly show symptoms such as runny nose, nasal congestion, headache and decreased sense of smell. At present, the industry believes that chronic sinusitis is related to multiple factors such as infection, inflammation, allergic reaction, and living environment pollution. These factors cause obstruction of the nasal cavity and sinus complex, causing edema of the sinus mucosa, capillary hyperplasia, and cell infiltration epithelial cilia shedding and polypoid degeneration, affecting the patient's ventilation and drainage. The course of the disease is long, up to 12 weeks, and it is easy to relapse.
[0003] At present, the diagnosis and treatment guidelines for chronic sinusitis recommend combined treatment with nasal spray hormone after nasal endoscopic surgery. Although this therapy has improved the recurrence rate of nasal polyps in chronic sinusitis to a certain extent, there are still many clinical studies that point out that the recurrence rate is still 12%-80%, and the reoperation rate is 3%-42%. If the eosinophil ratio is greater than 27%, the polyp recurrence rate is even higher. The high recurrence rate is not only related to the proficiency of nasal endoscopic surgery (FESS), but more importantly, it is difficult for nasal sprays to play a targeted role: because many studies have shown that the complex structure of the nasal cavity will significantly block the spray from entering the sinus surgery area, resulting in the sinus glucocorticoid spray spraying in the nasal cavity. All effective drugs cannot reach the sinus surgery area smoothly, and only less than 30% of the drugs can be unevenly delivered to the surgery area. The drug delivery efficiency is very low, which is not enough to achieve sufficient anti-inflammatory and anti-adhesion doses in the lesion surgery area, so many patients still have the risk of high postoperative recurrence rates such as mucosal inflammation, edema, and adhesions after FESS surgery.
[0004] Therefore, in view of the above problems, it is crucial to accurately deliver drugs to the lesion surgical area. At present, the targeted drug delivery products that have been launched at home and abroad - degradable sinus drug-loaded stents are widely recognized and used. Among them, the representative products are woven from high-molecular degradable polymer materials, with a cross-diamond hollow mesh structure. After implantation in the sinus lesion area, it can achieve a month of drug sustained release and degrade after one month. However, these products are all silk woven structures, with a small specific surface area and limited contact area with the surgical wound. In surgeries with a wide postoperative wound area such as Draf III, although they can be targeted for drug delivery, due to the small contact area with the postoperative wound, it is difficult to ensure that a large range of postoperative wounds are exposed to drugs, and it is also difficult to ensure that large wounds can achieve high drug loading per unit area, making it difficult for such "large wounds" to achieve good anti-inflammatory and anti-adhesion effects.
[0005] After FESS surgery, the above-mentioned degradable sinus drug-eluting stent that has been on the market can play a suitable role in physical support and fixation in the sinus surgery area. However, due to its hollow mesh structure, it is difficult for the entire wound surface to contact the stent body, and it cannot play a good physical barrier role, increasing the risk of wound adhesion; at the same time, its material is degradable, and it is difficult to achieve long-term stable support in the sinus surgery area, and it is also difficult to release drugs slowly for a long time; due to the "uneven main body" caused by degradation, many stent fragments of different sizes are produced, which further leads to unstable drug release.
[0006] Therefore, although the above-mentioned degradable sinus drug-loaded stents that have been marketed can achieve physical support, anti-adhesion, and drug release and anti-inflammatory effects, due to their degradability, patients still have the actual situation of "large wounds" with high recurrence rates and wound adhesions. This is not only related to low drug loading, inability to provide long-term stable support, and unstable drug release, but also related to their inability to guide the orderly regeneration of tissue in the sinus surgery area. Because the postoperative wound tissue is in the inflammatory response period and the mucosal transition competition stage, the unstable drug release and fragmented stents act as a foreign body stimulus, which makes it difficult to achieve the optimal natural physiological environment required for the repair of traumatic tissue, and it is difficult for the sinus mucosa to have a benign transition and to achieve normal epithelialization of the wound tissue.
[0007] Chinese patent documents with application numbers CN202022733544.2, CN202110296453.3, CN202311451317.2, CN202010353321.5, CN202311412483.1, etc. all involve sinus stents, but focus on how to improve the fit and firmness of the stent to the surgical area, how to improve the supporting force, how to delay the drug release cycle or resist adhesion and repair the mucosa. Most of them use degradable materials and mesh structures, and still have the defects of commercially available degradable sinus drug-eluting stents. The coated drug-loaded stent mentioned in Chinese patent document CN109394399A, which supports the lesion position after FESS surgery and continuously administers drugs, has a non-degradable membrane that needs to be sutured with surgical sutures and is provided with a traction line for the doctor to remove the stent. However, the preparation process of such a "sewing membrane" is complicated, and the unevenness and puncture of the "sewing membrane nodes" will aggravate the instability of drug release. At the same time, the presence of the traction line is not conducive to the discharge of foreign bodies in the narrow nasal cavity, and may further cause sinus obstruction. At the same time, relevant sinusitis diagnosis and treatment guidelines point out that double-dose treatment should be maintained for 4 months after FESS surgery, while the drug sustained-release coating of this patent achieves complete drug release in only 45 days. Such a targeted drug delivery cycle is not enough to completely restore the surgical wound surface, and the drug release cycle is short.
[0008] In summary, there is an urgent need for a sinus drug-loaded stent with a "large wound contact area, long-term stable support, long and stable drug release cycle, and the function of guiding tissue regeneration" in clinical practice. Therefore, the present invention will prepare a nasal membrane drug-loaded stent that can achieve stable drug release for 2 to 4 months, has a large wound contact area and long-term stable support, and can further guide tissue regeneration. The stent is suitable for sinus surgery areas with different spatial shapes, which not only further improves the clinical application defects of the sinus stent products on the market, but also fills the gap of no commercially available nasal membrane drug-loaded stent products. Summary of the invention
[0009] In view of the above problems existing in the nasal drug-carrying stent in the prior art, the present invention provides a nasal film-coated drug-carrying stent and a preparation method thereof.
[0010] In one aspect, the present invention provides a nasal membrane-covered drug-eluting stent, comprising:
[0011] Stent graft;
[0012] A drug coating, the drug coating is covered on the surface of the coated stent, the drug coating includes a therapeutic drug and a carrier thereof, wherein the carrier includes a first polymer and a second polymer, the first polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and its derivatives; the second polymer is selected from one or more of the following materials: glycolide-lactide copolymer (PLGA), polylactic acid (PLA), polycaprolactone (PCL), polyglycolic acid (PGA), chitosan, polyamino acid (PAA), polyethylene glycol (PEG), polyorthoester (POE) and its derivatives.
[0013] In some embodiments of the present invention, during the preparation of the drug coating, the therapeutic drug is not mixed with the first polymer and the second polymer simultaneously to form the drug coating solution.
[0014] In some embodiments of the present invention, the therapeutic drug is first formed into a mixed solution with one of the first polymer and the second polymer, and then the mixed solution is mixed with the other of the first polymer and the second polymer to form a drug coating solution; alternatively, the first polymer and the second polymer form a mixed solution and then are mixed with the therapeutic drug to form a drug coating solution.
[0015] In some embodiments of the present invention, the drug coating is coated on the surface of the stent graft from a drug coating solution through an ultrasonic spraying process.
[0016] In some embodiments of the present invention, the mass ratio of the first polymer to the second polymer is (1:9) to (7:3).
[0017] In some embodiments of the present invention, the therapeutic drug includes one or more of the following drugs: hormones, macrolides, antibacterial drugs, antitumor drugs, antibiotics; the mass percentage of the therapeutic drug in the drug coating solution is 0.1%-5%.
[0018] In some embodiments of the present invention, the stent graft comprises:
[0019] at least one bare stent, each bare stent having a first surface and a second surface opposite thereto, and made of a non-degradable material;
[0020] A first coating layer covers and adheres to a first surface of the bare stent;
[0021] A second covering layer, covering and adhering to the second surface of the bare stent;
[0022] The materials of the first coating layer and the second coating layer include non-degradable materials or degradable materials with a degradation period of more than 4 months.
[0023] In some embodiments of the present invention, the material of the at least one bare stent includes one or more of the following materials: nickel-titanium alloy, stainless steel, polyurethane, and silicone.
[0024] In some embodiments of the present invention, the materials of the first coating layer and the second coating layer include one or more of the following materials: expanded polytetrafluoroethylene film (ePTFE), silicone film, polyurethane film (TPU), polyester film, polyurethane film, gelatin film, polycaprolactone, lactic acid-hydroxyacetic acid copolymer, and polylactic acid.
[0025] In some embodiments of the present invention, the pore size and thickness of the first coating layer and the second coating layer are designed as follows: the membrane pore size of the first coating layer is larger than the membrane pore size of the second coating layer, and the thickness of the first coating layer is smaller than the thickness of the second coating layer.
[0026] In some embodiments of the present invention, the pore size and thickness of the first coating layer and the second coating layer are designed as follows: the membrane pore size of the second coating layer is 0.1-10 μm, and the thickness of the second coating layer is 30-100 μm.
[0027] In some embodiments of the present invention, the adhesive material used for the adhesion includes one or more of the following materials: polyurethane (TPU), fluorinated ethylene propylene (FEP), perfluoroalkyl (PFA), polyvinylidene fluoride (PVDF).
[0028] In some embodiments of the present invention, the nasal coated drug-eluting stent includes at least two bare stents arranged at intervals from each other.
[0029] In some embodiments of the present invention, the nasal film-covered drug-loaded stent also includes a guide layer, which covers the surface of the drug coating, and the guide layer includes a third polymer and a fourth polymer; the third polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and its derivatives; the fourth polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and its derivatives.
[0030] In some embodiments of the present invention, the mass ratio of the third polymer to the fourth polymer is (90:10) to (10:90).
[0031] In another aspect, the present invention provides a method for preparing a nasal film-coated drug-eluting stent, comprising the following steps:
[0032] (a) forming a stent graft having a first surface and a second surface opposite thereto;
[0033] (b) forming a drug coating on the first surface and the second surface of the coated stent; the drug coating is formed by a drug coating solution, which includes a therapeutic drug and a carrier thereof, wherein the carrier includes a first polymer and a second polymer, the first polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof; the second polymer is selected from one or more of the following materials: glycolide-lactide copolymer (PLGA), polylactic acid (PLA), polycaprolactone (PCL), polyglycolic acid (PGA), chitosan, polyamino acid (PAA), polyethylene glycol (PEG), polyorthoester (POE) and derivatives thereof.
[0034] In some embodiments of the present invention, in step (b), the preparation order of the drug coating solution is as follows: the therapeutic drug is first formed into a mixed solution with one of the first polymer and the second polymer, and then the mixed solution is mixed with the other of the first polymer and the second polymer to form a drug coating solution; or, the first polymer and the second polymer form a mixed solution and then are mixed with the therapeutic drug to form a drug coating solution.
[0035] In some embodiments of the present invention, in the drug coating solution, the mass ratio of the first polymer to the second polymer is (1:9) to (7:3).
[0036] In some embodiments of the present invention, in step (a), forming the stent graft comprises the following steps:
[0037] Providing at least one bare stent, each bare stent having a first surface and a second surface opposite thereto, and being made of a non-degradable material;
[0038] Covering the first surface and the second surface of the bare stent with a first coating layer and a second coating layer respectively, and adhering the coating layers to the first surface and the second surface of the bare stent by melt bonding, so as to form a coated stent;
[0039] The first coating layer and the second coating layer are made of non-degradable materials or degradable materials with a degradation period of more than 4 months.
[0040] In some embodiments of the present invention, in step (a), the material of the at least one bare stent includes one or more of the following materials: nickel-titanium alloy, stainless steel, polyurethane, and silicone.
[0041] In some embodiments of the present invention, in step (a), the materials of the first coating layer and the second coating layer include one or more of the following materials: expanded polytetrafluoroethylene film (ePTFE), silicone film, polyurethane film (TPU), polyester film, polyurethane film, gelatin film, polycaprolactone, lactic acid-glycolic acid copolymer, polylactic acid. The adhesive material used for the adhesion includes one or more of the following materials: polyurethane (TPU), fluorinated ethylene propylene (FEP), perfluoroalkyl compound (PFA), polyvinylidene fluoride (PVDF).
[0042] In some embodiments of the present invention, in step (a), the pore size and thickness of the first coating layer and the second coating layer are designed as follows: the membrane pore size of the first coating layer is larger than the membrane pore size of the second coating layer, and the thickness of the first coating layer is smaller than the thickness of the second coating layer.
[0043] In some embodiments of the present invention, in step (a), the pore size and thickness of the first coating layer and the second coating layer are designed as follows: the membrane pore size of the second coating layer is 0.1-10 μm, and the thickness of the second coating layer is 30 um-100 μm.
[0044] In some embodiments of the present invention, in step (a), at least two bare stents are selected so that the bare stents are arranged at intervals from each other.
[0045] In some embodiments of the present invention, the preparation method further includes step (c): forming a guide layer on the drug coating, wherein the guide layer is formed by a guide layer solution, and the guide layer solution includes a third polymer and a fourth polymer; wherein the third polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof; and the fourth polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof; wherein the mass ratio of the third polymer to the fourth polymer is 90:10 to 10:90.
[0046] In some embodiments of the present invention, in step (b), the drug coating solution is coated on the surface of the stent graft by an ultrasonic spraying process; in step (c), the guide layer solution is coated on the surface of the drug coating by an ultrasonic spraying process.
[0047] Compared with the prior art, the present invention has the following beneficial technical effects:
[0048] 1. The coated drug-loaded stent of the present invention has a large contact area with the wound surface, and while achieving targeted and precise drug delivery, it can ensure the postoperative repair contact area and high drug loading for large wound surgeries such as Draf III frontal sinus surgery. Therefore, it has better anti-inflammatory and anti-adhesion effects for large wound repair.
[0049] 2. The drug coating covering the surface of the coated stent of the present invention can regulate the drug release cycle to the desired duration of nasal wound repair through the design of the drug carrier, so that the drug release during the wound repair period is more stable, long-lasting and controllable. The duration of continuous and stable drug release can reach 2-4 months, which can well meet the needs of nasal wound repair.
[0050] 3. When a tissue regeneration guiding layer is provided on the drug coating of the coated drug-eluting stent of the present invention, it can guide the directional growth of wound tissue and prevent abnormal conditions such as coral-like polyps, and has a good therapeutic effect on wound restenosis in patients with high recurrence and large wounds.
[0051] 4. The coated drug-eluting stent of the present invention uses non-degradable materials as the coated stent, and ensures the firmness of the coating by bonding, thereby achieving long-term and stable support for the wound surface. In addition, the drug coating of the coated drug-eluting stent of the present invention has a "microcapsule-like" structure that can achieve sustained drug release, so that it can still maintain stable and long-term drug release behavior while ensuring a high drug loading, and the drug can be fully released for up to 4 months. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a drug release curve diagram of the coated drug-eluting stents of Examples 1-4 of the present invention and Comparative Examples 1 and 2.
[0053] Figure 2 It is a drug release curve diagram of the coated drug-eluting stent of Examples 4-8 of the present invention.
[0054] Figure 3 3 is a graph showing the peeling force test results of the drug-eluting stent coated in Example 4 of the present invention.
[0055] Figure 4 The initial state of wound contact when a commercially available competitor stent was implanted into the maxillary sinus of a beagle dog.
[0056] Figure 5 This is the initial state of wound contact of the coated drug-eluting stent implanted in the maxillary sinus of a beagle dog according to Example 4 of the present invention.
[0057] Figure 6 The wound surface condition of a commercially available competitor stent implanted in the maxillary sinus of a beagle dog 14 days ago.
[0058] Figure 7 The wound surface condition of the coated drug-eluting stent of Example 4 implanted in the maxillary sinus of a beagle dog for 14 days.
[0059] Figure 8 It is a diagram showing the change in the stent support force of the drug-eluting stents of Example 1, Example 4 and Comparative Example 2 of the present invention after being immersed in simulated body fluid-PBS.
[0060] Fig. 9 This is a picture of the wound recovery after a competitive stent was implanted in the maxillary sinus of a beagle dog one month ago.
[0061] Fig.10 This is a diagram showing the wound recovery of the coated drug-eluting stent according to Example 4 of the present invention implanted in the maxillary sinus of a beagle dog for 4 months.
[0062] Fig.11 This is a HE staining image of the mucosal tissue in contact with the stent after the coated drug-eluting stent of Example 4 of the present invention was implanted in the maxillary sinus of a beagle dog for one month.
[0063] Fig.12 This is the HE staining image of the mucosal tissue in contact with the stent after the coated drug-eluting stent of comparative example 3 was implanted in the maxillary sinus of a beagle dog for one month. DETAILED DESCRIPTION
[0064] Various aspects of the present invention will be described in detail below in conjunction with specific embodiments. These specific embodiments are only used to illustrate the present invention and do not constitute any limitation on the protection scope of the present invention.
[0065] In a specific embodiment of the present invention, the preparation of the stent graft includes:
[0066] (1) Select two layers of membrane materials that can be used for stent coating, cut them to a suitable size, and perform coating to form a coating layer using the following steps. The two coating layers can be made of the same material or different materials. Among them, the membrane material of the coating layer can be a non-degradable membrane material such as expanded polytetrafluoroethylene membrane (ePTFE), silicone membrane, polyurethane membrane (TPU), polyester membrane, etc., or a degradable membrane such as polyurethane membrane, gelatin membrane, polycaprolactone, lactic acid-glycolic acid copolymer, polylactic acid, etc. Among them, a non-degradable membrane is preferred to ensure long-term plastic effect on the wound surface after surgery; if the membrane material is a non-degradable membrane, a membrane material model with a long degradation period (at least 4 months) must be used to ensure the integrity of the membrane material when the stent is removed from the nasal cavity. In a specific embodiment of the present invention, both coating layers are ePTFE membranes.
[0067] (2) By applying, scraping, laying, etc., a solution or film of a melt-processable adhesive material (such as polyurethane (TPU), fluorinated ethylene propylene (FEP), perfluoroalkyl compound (PFA), polyvinylidene fluoride (PVDF), etc.) is placed between two layers of cut films.
[0068] (3) Then one or more bare stents are placed between two layers of film materials with the above-mentioned adhesive material to form a prototype coated stent. A certain gap is maintained between the multiple bare stents, which is conducive to the coated stent being more flexible when conforming to the shape of the nasal cavity. The bare stent material can be a non-degradable stent made of any material such as nickel-titanium alloy, stainless steel, polyurethane, silicone, etc. The stent can also have a temperature-sensitive function. In the specific embodiment of the present invention, a nickel-titanium alloy stent is selected, and a nickel-titanium alloy wire with a phase change temperature between 20-28°C is selected. Through heating and shaping treatment, the stent is in an austenitic state at 30-37°C, has sufficient supporting force, and plays a supporting role. Before implanting the nasal cavity and when the stent is removed after the therapeutic effect is achieved, rinse with cold saline or ice to make the stent in a martensitic state, which is soft and weak, and can be easily implanted and removed. The shape of the stent is not limited, and all sinus stents available on the market can be used; the present invention preferably has multiple stents, which are prepared into an integrated structure through the above coating process. Such a stent is like a soft water pipe with multiple edges. After implanting the nasal cavity, it can be instantly plastic according to the shape of the nasal cavity and has good compliance.
[0069] (4) The above-mentioned prototype coated stent is placed in an oven for gradient heating, melted and bonded at 150-300°C, and placed in a vacuum drying oven after stabilization for 10-60 minutes at 5-15°C and a vacuum degree of -0.6 to -1 bar. The temperature is rapidly cooled and vacuumed, that is, through the form of "heating and sudden cooling, and sudden drop in air pressure", a coated stent with a very strong bond between the film material and the metal stent is obtained, which is not easy to block excrement. The pore size and thickness of the two coating layers are different. The pore size of the membrane inside the stent is larger than that of the outer membrane, and the thickness of the inner membrane of the stent is smaller than that of the outer membrane. The pore size of the outer membrane outside the stent can be 0.1-10um, and the thickness of the outer membrane of the stent can be 30um-100um. After the "heating and sudden cooling, and sudden drop in air pressure" treatment, the metal wire of the stent is completely infiltrated and wrapped by the high-temperature molten adhesive material, thereby being firmly bonded, making it difficult to separate the metal wire and the membrane, which is safer; at the same time, due to the large pore size and small thickness of the inner membrane of the stent, the inner membrane of the stent is easily immersed in the adhesive material and presents a bright state, and the inside is very smooth and not astringent. When used in the nasal cavity, it is more conducive to the discharge of foreign matter and is not easy to be blocked.
[0070] In the coated stent prepared by the above coating method, the non-degradable nickel-titanium alloy can provide long-term stable support, and the wide membrane area can provide a large wound contact area.
[0071] In a specific embodiment of the present invention, the preparation of the drug coating comprises:
[0072] A drug coating is formed on the surface of the coated stent, wherein the drug carrier includes a first polymer and a second polymer, which are selected from two or more polymers selected from poly(lactic acid)-poly(vinylpyrrolidone) (PLGA), polylactic acid, gelatin, polycaprolactone, polyethylene glycol, polyurethane (TPU) or their copolymers. The drug loading and release mechanisms of the first polymer and the second polymer are different. In a specific embodiment of the present invention, the first polymer is TPU and the second polymer is PLGA. TPU releases the drug after swelling with water through the pores, and PLGA releases the drug through its own dissolution and degradation. The therapeutic drug is one or more of hormones, macrolides, antibacterial drugs, antitumor drugs, and antibiotics. In an embodiment of the present invention, the therapeutic drug is mometasone furoate. The drug coating method is one or more of spraying, dipping, spin coating, and scraping.
[0073] The drug release cycle can be regulated by controlling the ratio of the first polymer to the second polymer. In a specific embodiment of the present invention, the mass ratio of TPU to PLGA can be 1:9-7:3, the mass ratio of the drug to PLGA is 1:1-1:10, the final concentration of the drug and the carrier mixture in the solution for forming the drug coating is 0.5-10%, the solvent is acetone, the concentration of mometasone furoate (MF) is 0.1%-5%, the ratio of the drug to the two polymers is 1:2-1:20, the ratio of LA to GA in PLGA can be all product forms on the market (such as 10:90, 85:15, 75:25, 50:50, 25:75, 15:85, 90:10, etc.), TPU can be all product forms on the market that can be used for intervention and implantation (such as polyester, polyether, etc.), and can be in a degradable form or a non-degradable form. The solution required to form the drug coating is sprayed by ultrasonic spraying. The equipment can produce atomized droplets that meet the particle size of microcapsules, and prepare the drug coating into a "microcapsule-like" structure. The "microcapsule-like" is composed of one or more capsule cores and capsule walls, with a particle size between 1 and 250 μm, and can exert a drug sustained-release effect similar to that of "microcapsules"; the coating thickness is 0.005 to 0.1 mm.
[0074] The preparation of the solution for forming the drug coating requires that the first polymer and the second polymer cannot be mixed with the drug at the same time, so that the drug release mechanisms of the two polymers compensate each other, thereby regulating the drug release cycle. In other words, the solution preparation sequence must be sequential, and the three substances cannot be dissolved together. In a specific embodiment of the present invention, PLGA-MF can be mixed and dissolved first, and then mixed with the TPU solution, so that one polymer and part of the drug form a first capsule core, and another polymer then wraps the drug that is not completely wrapped in the capsule core and the first capsule core to form a second capsule core. While the first capsule core and the second capsule core are physically superimposed, the polymer also forms a capsule wall to form a "microcapsule-like" structure. In this way, the drug located in the capsule wall but not in the first capsule core material and the second capsule core material will be released due to the enlarged pores of TPU after it absorbs water and swells. Gradually, the drug wrapped in the second capsule core material will be further released due to the degradation and dissolution of PLGA and the continued swelling of TPU. Gradually, the drug wrapped in the first capsule core material will continue to be further released due to the degradation and dissolution of PLGA and the continued swelling of TPU. Finally, due to the different lengths of the TPU pores in the capsule wall and the capsule core material and the degradation and dissolution rates of PLGA, the coated drug-eluting stent obtains different drug release rates.
[0075] In the preparation process of drug coating, it is easier to prepare a "microcapsule-like" structure with sustained release function by controlling the ultrasonic spraying parameters. For example, the following spraying parameters can be controlled: spraying liquid viscosity ≤15cps, ultrasonic nozzle frequency ≥50HZ, the temperature of the drying system must be maintained between 30-55°C, and the liquid inlet rate must be maintained at 0.05-1mL / min.
[0076] In a specific embodiment of the present invention, according to the above preparation method, taking a stent with a diameter of 25 mm and a total length of 14 mm as an example, the dose density (drug loading amount expressed as dose density) can reach 0.91-9.10 ug / mm 2 , and can achieve a sustained release cycle of 4 months of drug release. Due to the presence of TPU in the drug coating, the carbamate in its structure can significantly improve the adhesion and wettability of the prototype coated stent, which significantly improves the firmness of the drug coating; the outer membrane of the prototype coated stent has certain pore size requirements, which allows the TPU in the coating to infiltrate into the outer membrane through the pore size, further improving the firmness of the drug coating. The improvement of the firmness of the drug coating makes the drug sustained release cycle more stable and controllable.
[0077] In a specific embodiment of the present invention, a guide layer can also be formed on the drug coating, and the guide layer is a combination of one or more of TPU, nano-silica, polyethylene glycol (PEG) magnesium stearate, talcum powder, and sodium lauryl sulfate. In a specific embodiment of the present invention, the guide layer includes a third polymer TPU and a fourth polymer PEG.
[0078] In a specific embodiment of the present invention, the solution for forming the guiding layer is prepared as follows: the mass ratio of TPU to PEG can be 1:9 to 9:1, the final concentration of the mixture is 0.5 to 20%, the solvent is acetone, and the mixture is dissolved. PEG can be selected from a variety of molecular weights, such as PEG 600, PEG 1000, PEG 1500, PEG 2000, PEG 3350, PEG 4000, PEG 6000, PEG 10000, PEG 20000, PEG 40000, etc.
[0079] The mixed solution is ultrasonically sprayed to form a guide layer.
[0080] In a specific embodiment of the present invention, the guide layer is composed of TPU and PEG. TPU itself is a mesh structure, which can carry and release drugs, but its mesh structure is not fibrous, making it difficult for cells to adhere and grow in a directional manner. After adding PEG, it will occupy the TPU pores until it fills the TPU pores. With its slow degradation and the gradual swelling of TPU, the TPU, which was originally a simple mesh structure, will present a fiber mesh structure with clear boundaries and significant spatial structure due to the presence of PEG, thereby having the function of guiding the directional growth of cells; the thickness of the guide layer is much smaller than the drug coating. In the process of forming the fiber mesh structure, its mesh shape does not affect the drug release of the drug coating, and the anti-inflammatory and anti-adhesion drug effects continue to play a role. The thickness of the guide layer can be 5%-15% of the thickness of the drug coating. In a specific embodiment of the present invention, the thickness of the guide layer is 10% of the thickness of the drug coating, and the total thickness of the drug coating and the guide layer is between 5um-50um.
[0081] In addition, PEG has excellent water solubility, anti-adsorption and biocompatibility. When it adheres to the surface of the material, it can form a hydration layer, thereby effectively reducing the adsorption of proteins and bacteria. Therefore, the presence of PEG in the coated drug-eluting stent can also effectively prevent bacterial infection and inflammation in the sinus surgery area.
[0082] After the preparation, the drug coating and the guide layer are both subjected to vacuum drying for 1 to 3 hours to completely remove the solvent therein.
[0083] The present invention is described in detail below with reference to specific embodiments.
[0084] Example 1
[0085] The preparation of the coated drug-eluting stent of this embodiment includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0086] (1) Preparation of stent graft:
[0087] FEP with a melting point of 180°C is placed between two layers of ePTFE membranes, the inner ePTFE membrane is 15 μm thick and has a pore size of 0.3 μm, and the outer ePTFE membrane is 40 μm thick and has a pore size of 0.15 μm;
[0088] Two hollow cylindrical nickel-titanium alloy stents were placed between two layers of ePTFE membranes covered with FEP to form an ePTFE prototype covered stent with a diameter of 25 mm and a total length of 14 mm.
[0089] The above prototype ePTFE coated stent was placed in an oven with gradient heating, and melt-bonded at 250°C for 20 minutes;
[0090] After melt bonding, the ePTFE prototype coated stent is taken out of the oven and quickly placed in a vacuum drying oven. It is quickly cooled and vacuumed at 5°C and a vacuum degree of -0.6 bar to obtain an ePTFE coated stent with a shiny inner layer and good firmness.
[0091] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0092] Preparation of PLGA 8515-MF (mometasone furoate) solution: using acetone as solvent, adding PLGA 8515 and mometasone furoate (MF), fully dissolving them to form a PLGA 8515-MF solution;
[0093] Prepare TPU solution: use acetone as solvent and add TPU to form TPU solution;
[0094] Preparation of drug coating solution: Stir and mix the PLGA 8515-MF solution and the TPU solution to obtain a drug coating solution. In the drug coating solution, the total mass percentage concentration of TPU, PLGA and MF is 0.5%, wherein the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.28%, the mass percentage concentration of PLGA 8515 is 0.12%, and the mass ratio of TPU to PLGA is: TPU:PLGA=7:3;
[0095] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a dose density of 2.73 μg / mm 2 The drug coating (drug loading is expressed as dose density). The process parameters of ultrasonic spraying are: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0096] (3) forming a guide layer on the drug coating formed in step (2):
[0097] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.5%, and the mass percentage concentration of PEG 6000 is 0.5%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 1:1;
[0098] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0099] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0100] Example 2
[0101] The preparation of the drug-eluting stent in this embodiment includes the preparation of the drug-eluting stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0102] (1) Preparation of stent graft:
[0103] The preparation method of the coated stent is the same as that in Example 1.
[0104] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0105] Preparation of TPU-MF solution: using acetone as solvent, adding TPU and mometasone furoate (MF), fully dissolving them to form a TPU-MF solution;
[0106] Preparation of drug coating solution: dissolve PLGA 8515 in TPU-MF solution, stir and mix evenly, so as to prepare drug coating solution. In the drug coating solution, the total mass percentage concentration of TPU, PLGA and MF is 0.5%, wherein the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.28%, the mass percentage concentration of PLGA 8515 is 0.12%, and the mass ratio of TPU to PLGA is: TPU:PLGA=7:3;
[0107] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0108] (3) forming a guide layer on the drug coating formed in step (2):
[0109] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.5%, and the mass percentage concentration of PEG 6000 is 0.5%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 1:1;
[0110] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0111] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0112] Example 3
[0113] The preparation of the coated drug-eluting stent of this embodiment includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0114] (1) Preparation of stent graft:
[0115] The preparation method of the coated stent is the same as that in Example 1.
[0116] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0117] Preparation of PLGA 8515-TPU solution: using acetone as solvent, adding PLGA 8515 and TPU, fully dissolving them to form a PLGA 8515-TPU solution;
[0118] Preparation of drug coating solution: Dissolve MF in PLGA 8515-TPU solution and stir to mix well, thus preparing drug coating solution. In the drug coating solution, the total mass percentage concentration of TPU, PLGA and MF is 0.5%, among which the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.28%, the mass percentage concentration of PLGA 8515 is 0.12%, and the mass ratio of TPU to PLGA is: TPU:PLGA=7:3;
[0119] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2 The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0120] (3) forming a guide layer on the drug coating formed in step (2):
[0121] Prepare the guiding layer solution: use acetone as solvent, add TPU and PEG 6000, mix and dissolve to form a guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.5%, and the mass percentage concentration of PEG 6000 is 0.5%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 1:1;
[0122] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0123] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0124] Example 4
[0125] The preparation of the coated drug-eluting stent of this embodiment includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0126] (1) Preparation of stent graft:
[0127] TPU with a melting point of 180°C is placed between two layers of ePTFE membranes, the inner ePTFE membrane is 15 μm thick and has a pore size of 0.3 μm, and the outer ePTFE membrane is 40 μm thick and has a pore size of 0.15 μm;
[0128] Two hollow cylindrical nickel-titanium alloy stents were placed between two layers of ePTFE membranes covered with TPU to form an ePTFE prototype covered stent with a diameter of 25 mm and a total length of 14 mm.
[0129] The above prototype ePTFE coated stent was placed in an oven with gradient heating, and melt-bonded at 250°C for 20 minutes;
[0130] After melt bonding, the ePTFE prototype coated stent is taken out of the oven and quickly placed in a vacuum drying oven. It is quickly cooled and vacuumed at 5°C and a vacuum degree of -0.6 bar to obtain an ePTFE coated stent with a bright inner layer and good firmness.
[0131] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0132] Preparation of PLGA 8515-MF solution: using acetone as solvent, adding PLGA 8515 and mometasone furoate (MF), fully dissolving them to form a PLGA 8515-MF solution;
[0133] Prepare TPU solution: use acetone as solvent and add TPU to form TPU solution;
[0134] Preparation of drug coating solution: Stir and mix the PLGA 8515-MF solution and the TPU solution to obtain a drug coating solution. In the drug coating solution, the total mass percentage concentration of TPU, PLGA and MF is 0.5%, wherein the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.28%, and the mass percentage concentration of PLGA 8515 is 0.12%, which is equivalent to the solid content ratio of TPU to PLGA being: TPU:PLGA=7:3;
[0135] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2 The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0136] (3) forming a guide layer on the drug coating formed in step (2):
[0137] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.5%, and the mass percentage concentration of PEG 6000 is 0.5%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 1:1;
[0138] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0139] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0140] Example 5
[0141] The preparation of the coated drug-eluting stent of this embodiment includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0142] (1) Preparation of stent graft:
[0143] The preparation method of the coated stent is the same as that of Example 4.
[0144] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0145] Preparation of PLGA 8515-MF solution: using acetone as solvent, adding PLGA 8515 and mometasone furoate (MF), fully dissolving them to form a PLGA 8515-MF solution;
[0146] Prepare TPU solution: use acetone as solvent and add TPU to form TPU solution;
[0147] Preparation of drug coating solution: Stirring and mixing PLGA 8515-MF solution and TPU solution, a drug coating solution is prepared. In the drug coating solution, the total mass percentage concentration of TPU, PLGA 8515 and MF is 0.5%, wherein the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.04%, the mass percentage concentration of PLGA 8515 is 0.36%, and the mass ratio of TPU to PLGA is: TPU:PLGA=1:9;
[0148] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2 The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0149] (3) forming a guide layer on the drug coating formed in step (2):
[0150] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.5%, and the mass percentage concentration of PEG 6000 is 0.5%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 1:1;
[0151] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0152] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0153] Example 6
[0154] The preparation of the coated drug-eluting stent of this embodiment includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0155] (1) Preparation of stent graft:
[0156] The preparation method of the coated stent is the same as that of Example 4.
[0157] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0158] Preparation of PLGA 8515-MF solution: using acetone as solvent, adding PLGA 8515 and mometasone furoate (MF), fully dissolving them to form a PLGA 8515-MF solution;
[0159] Prepare TPU solution: use acetone as solvent and add TPU to form TPU solution;
[0160] Preparation of drug coating solution: Stir and mix the PLGA 8515-MF solution and the TPU solution to obtain a drug coating solution. In the drug coating solution, the total mass percentage concentration of TPU, PLGA 8515 and MF is 0.5%, wherein the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.2%, the mass percentage concentration of PLGA 8515 is 0.2%, and the mass ratio of TPU to PLGA is: TPU:PLGA=1:1;
[0161] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2 The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0162] (3) forming a guide layer on the drug coating formed in step (2):
[0163] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.5%, and the mass percentage concentration of PEG 6000 is 0.5%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 1:1;
[0164] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0165] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0166] Example 7
[0167] The preparation of the coated drug-eluting stent of this embodiment includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0168] (1) Preparation of stent graft:
[0169] The preparation method of the coated stent is the same as that of Example 4.
[0170] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0171] The preparation method of the drug coating is the same as that of Example 4.
[0172] (3) forming a guide layer on the drug coating formed in step (2):
[0173] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.9%, and the mass percentage concentration of PEG 6000 is 0.1%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 9:1;
[0174] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0175] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0176] Example 8
[0177] The preparation of the coated drug-eluting stent of this embodiment includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0178] (1) Preparation of stent graft:
[0179] The preparation method of the coated stent is the same as that of Example 4.
[0180] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0181] The preparation method of the drug coating is the same as that of Example 4.
[0182] (3) forming a guide layer on the drug coating formed in step (2):
[0183] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.1%, and the mass percentage concentration of PEG 6000 is 0.9%, which is equivalent to a solid content ratio of TPU to PEG 6000 of 1:9.
[0184] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0185] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0186] Comparative Example 1
[0187] The preparation of the coated drug-eluting stent of this comparative example includes the preparation of the coated stent, the preparation of the drug coating and the preparation of the guide layer, which specifically includes the following steps:
[0188] (1) Preparation of stent graft:
[0189] The preparation method of the coated stent is the same as that of Example 4.
[0190] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0191] Preparation of drug coating solution: Using acetone as solvent, PLGA 8515, TPU and MF are dissolved in acetone at the same time to obtain a drug coating solution. In the drug coating solution, the total mass percentage concentration of TPU, PLGA and MF is 0.5%, wherein the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.28%, the mass percentage concentration of PLGA 8515 is 0.12%, and the mass ratio of TPU to PLGA is: TPU:PLGA=7:3;
[0192] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2 The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0193] (3) forming a guide layer on the drug coating formed in step (2):
[0194] Preparation of guiding layer solution: using acetone as solvent, adding TPU and PEG 6000, mixing and dissolving to form guiding layer solution. In the guiding layer solution, the total mass percentage concentration of TPU and PEG 6000 is 1%, wherein the mass percentage concentration of TPU is 0.5%, and the mass percentage concentration of PEG 6000 is 0.5%, which is equivalent to a solid content ratio of 1:1;
[0195] The guiding layer solution was sprayed on the drug coating by ultrasonic spraying to obtain a tissue guiding layer with a thickness of 0.005 mm. The process parameters of ultrasonic spraying of the guiding layer were as follows: spraying liquid viscosity 7 cps, frequency 100 Hz, drying system temperature 35 °C, and liquid feeding speed 0.05 mL / min;
[0196] After the guide layer is formed, the coated drug-eluting stent is vacuum dried for 3 hours to completely remove the solvent.
[0197] Comparative Example 2
[0198] (1) Preparation of scaffold:
[0199] The stent body is a hollow cylinder with two open ends obtained by 3D printing of degradable polylactide-polylactide (PLGA) polymer threads, which presents multiple diamond-shaped mesh structures. The thread diameter is 0.3mm, the stent diameter is 25mm, and the length is 14mm.
[0200] The diamond mesh structure is arranged in two rows in the axial direction of the support, and the number of diamonds in each row is 8.
[0201] (2) forming a drug coating on the surface of the stent prepared in step (1):
[0202] Preparation of drug coating solution: using acetone as solvent, dissolving PLGA 8515 in acetone to form a PLGA 8515 solution with a PLGA 8515 mass percentage concentration of 0.5%, and then dissolving MF in the PLGA 8515 solution with a concentration of 1%.
[0203] The drug coating solution was sprayed on the stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2 The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0204] After the drug coating is formed, the stent is vacuum dried for 3 h to completely remove the solvent.
[0205] Comparative Example 3
[0206] The preparation of the coated drug-eluting stent of this comparative example includes the preparation of the coated stent and the preparation of the drug coating, which specifically includes the following steps:
[0207] (1) Preparation of stent graft:
[0208] The preparation method of the coated stent is the same as that of Example 4.
[0209] (2) forming a drug coating on the surface of the stent graft prepared in step (1):
[0210] Preparation of PLGA 8515-MF solution: using acetone as solvent, adding PLGA 8515 and mometasone furoate (MF), fully dissolving them to form a PLGA 8515-MF solution;
[0211] Prepare TPU solution: use acetone as solvent and add TPU to form TPU solution;
[0212] Preparation of drug coating solution: Stir and mix the PLGA 8515-MF solution and the TPU solution to obtain a drug coating solution. In the drug coating solution, the total mass percentage concentration of TPU, PLGA and MF is 0.5%, wherein the mass percentage concentration of MF is 0.1%, the mass percentage concentration of TPU is 0.28%, the mass percentage concentration of PLGA 8515 is 0.12%, and the mass ratio of TPU to PLGA is: TPU:PLGA=7:3.
[0213] The drug coating solution was sprayed on the ePTFE coated stent prepared in step (1) by ultrasonic spraying to obtain a coating with a thickness of 0.05 mm and a drug loading per unit area of 2.73 μg / mm 2 The process parameters of ultrasonic spraying are as follows: spraying liquid viscosity 7cps, frequency 100Hz, drying system temperature 35℃, and liquid feeding speed 0.05mL / min.
[0214] After the drug coating is formed, the coated drug-loaded stent is vacuum dried for 3 hours to completely remove the solvent.
[0215] In order to further illustrate the beneficial technical effects of the nasal coated drug-loaded stent of the present invention, the performance of the nasal coated drug-loaded stent prepared by the specific embodiment of the present invention will be tested and evaluated below, including drug release test, peeling force test, wound contact test, stent mechanical property test, wound repair test, scanning electron microscopy test, HE staining and drug-loaded layer microstructure test.
[0216] 1. Drug Release Assay
[0217] Determination method: The drug content was detected by liquid phase method. Each group of stents (Examples 1-8, Comparative Examples 1-2) was simulated for storage-ejection using a conveyor, placed in a 250ml conical flask containing 200ml of release medium, placed in a shaker at 37±0.5°C, with a rotation speed of 80r / min, and protected from light. 4ml of the dissolution solution was respectively aspirated for liquid phase detection at weeks 0, 1, 2, 3, 4, 6, 8, 12, and 16, and an equal volume of release medium was added after each sampling.
[0218] The drug release test results of Examples 1-4 and Comparative Examples 1-2 are as follows: Figure 1As shown. In Example 1 and Example 4, by selecting polymers with different drug loading and release mechanisms and specially regulating the solution preparation sequence, the drug release is effectively regulated to prepare a drug coating with a "microcapsule-like" structure having a two-layer capsule core. It can be seen from the drug release curve that the coated drug-loaded stents of Example 1 and Example 4 can quickly release drugs in the early stage of surgery to play a therapeutic role, and begin to release drugs steadily after the 4th week until the cumulative drug release reaches at least 95% in the 16th week, playing a long-term anti-inflammatory and anti-adhesion role, that is, the drug treatment effect of the coated drug-loaded stent can last for 4 months to prevent recurrence in the surgical area.
[0219] In Example 2 and Example 3, by changing the preparation order of the solution, a drug coating with a "microcapsule-like" structure having a single-layer capsule core is prepared, and the drug release time can be adjusted to 2-3 months. For patients with less severe sinusitis and relatively small wounds, this type of coated drug-loaded stent can also effectively prevent recurrence in the surgical area. However, the time for the coated drug-loaded stents in Example 2 and Example 3 to achieve 80% drug release and stable release is different. This is because in Example 2, TPU first stores drugs in the pores, and then relies on PLGA to randomly grab the drugs in the pores to wrap and form a capsule core, while in Example 3, PLGA and TPU are compounded together, and the two drug-loading matrices with very different drug loading effects compensate each other, have a stronger ability to grab drugs, so that more drugs are wrapped in the capsule core, and have a relatively good ability to control rapid release.
[0220] Comparative Example 1 Compared with Example 1 or Example 4, Comparative Example 1 mixes and dissolves PLGA, TPU and the drug at the same time, without making a special setting for the preparation order of the solution. The coated drug-loaded stent of Comparative Example 1 has a serious burst release around the second week of drug release, with a cumulative release of about 80% of the drug, and the drug release trend is poorly parallel, unstable, and the drug release cycle is very short. It is basically released completely in about 4 weeks, which is difficult to meet the demand for drug release cycle for nasal wound repair. This is because after the three substances are directly mixed, the two drug-loaded matrices are not "additively loaded", but "competitively loaded", that is, the drug-loaded matrix with a large proportion is dominant, and it is difficult to achieve long-term sustained release of the drug. Therefore, only by regulating the solution preparation order, the two drug-loaded matrices can reflect the "additive loading" mode, play their respective roles together, and prepare a "microcapsule-like" structure, thereby significantly extending the drug release cycle of the drug coating and controlling the drug release cycle within the desired range. The stent of Comparative Example 2 achieves 80% drug release around the third week, and the drug release is relatively slow after 3 weeks, and the drug release cycle is only about 1 month.
[0221] The in vitro drug release test results of Examples 4-8 are as follows Figure 2 As shown. Figure 2It can be seen that the release rate of the coated drug-eluting stent of Examples 4-8 in the first 4 weeks is faster than the release rate after 4 weeks, and the release cycle lasts for about 4 months.
[0222] In the coated drug-loaded stent of Example 4-6, the mass percentage of TPU and PLGA in the drug coating solution is controlled at 1:9 to 7:3, and the drug coating solution adopts the same preparation order, and the drug release time can be regulated to about 4 months. There is a certain difference in their drug release rate after 4 weeks, that is, there is a certain difference in the release trend after reaching 80% release. It can be seen that with the increase of PLGA proportion, the release time of the drug to reach 100% is gradually prolonged. This is because the drug release in the first 4 weeks is mainly the pore swelling release of TPU and the drug on the outer wall of the PLGA capsule core. Due to the concentration difference, the release rate will be relatively faster; and the drug released after 4 weeks is mainly the drug stored in the PLGA capsule core. The gradual degradation of PLGA causes it to slowly release the drug in the capsule core. With the increase of PLGA content in the drug coating, the release rate of the drug after 80% release slows down.
[0223] Compared with Examples 7-8, Example 4 has the same drug coating and different guiding layers, but the differences in each stage of drug release in vitro are very small, indicating that the guiding layer in the coated drug-eluting stent has little effect on drug release.
[0224] 2. Peel force test:
[0225] Test method: Tested with a universal tester (n=3). Clamp the upper and lower layers of the film of the drug-eluting stent to be tested at the film interface with clamps respectively, and test it on a universal testing machine at a displacement speed of 50mm / min, and record the maximum peeling force. The specifications of the measured stent are 25mm in diameter and 14mm in height, which are the same as the specifications of commercially available competing products. The test samples are the drug-eluting stents prepared in Example 4, as well as the samples after they were immersed in simulated body fluid-PBS for 1 month, 2 months, and 4 months (n=3). The extraction conditions are the same as the drug release test conditions above. The peeling test results are as follows. Figure 3 shown.
[0226] from Figure 3 It can be seen that the peeling force of the coated drug-eluting stent of Example 4 does not change substantially during the immersion period of 4 months, and even after being immersed in simulated body fluids, the coating firmness can still be maintained very well.
[0227] 3. Wound contact test
[0228] Test method: The commercially available stent competitor and the stent prepared in Example 4 were implanted into the left and right maxillary sinuses of beagles, and the two stents were of the same size. Before implantation, the beagles were first injected with intramuscular ceftiofur sodium and subcutaneous meloxicam for surgical anti-inflammatory and surgical analgesia, respectively; atomization anesthesia was performed; then, with the help of endoscopy, the maxillary sinus was treated with nasal polyp forceps, bent needles, etc. (using a bent 1mL syringe needle to longitudinally scrape the maxillary sinus mucosa on all four sides of the inner wall of the maxillary sinus, and after conventional compression and hemostasis, the stent was implanted into the maxillary sinus using a delivery device); after implantation, intramuscular injection of ceftiofur sodium was used for postoperative anti-inflammatory treatment once a day for 5 consecutive days; subcutaneous injection of meloxicam was used for postoperative analgesia once a day; and the nasal cavity was cleaned with physiological seawater every day.
[0229] After implanting the stent, observe the contact between the stent and the wound surface. Figure 4 and Figure 5 As shown, Figure 4 The initial state of contact with the wound surface where the commercial competitor product is implanted. Figure 5 The wound surface is in the initial state after implanting the coated drug-eluting stent prepared in Example 4. Figure 4 and Figure 5 It can be seen that after the implantation of the competing product on the market, only the silk thread contacts the wound surface, and the hollow mesh part is difficult to contact the wound surface; however, after the implantation of the coated drug-eluting stent prepared in Example 4, due to the wide wound contact area provided by the ePTFE membrane material, the surgical wound is completely in contact with the coated drug-eluting stent, ensuring that every wound is in contact with the drug, achieving anti-inflammatory and anti-adhesion effects.
[0230] 14 days after implantation, the contact between the stent and the wound surface was observed by nasal endoscopy. Figure 7 and Figure 8 As shown, Figure 7 The wound contact of the commercial competitor was 14 days after implantation. Figure 8 The wound contact condition after implantation of the coated drug-eluting stent of Example 4 for 14 days. Figure 7 and Figure 8 It can be seen that the contact between the stents of competing products on the market and the wound surface is not good, and the stent fragments are stuck inside the surgical area, which cannot ensure that the stent is in full contact with the wound surface. The stent of Example 4 has a strong coating structure and a large area, providing a good long-term stable support force, and has a very good adhesion to the wound surface, which greatly ensures the precise delivery of drugs to large wounds and ensures the stability of drug release.
[0231] It can be seen from the above experiments that the coated drug-eluting stent of Example 4 fits well and completely on the wound surface of the surgical area, providing long-term support and good stent firmness.
[0232] 4.Stent mechanical properties test
[0233] Test method: Use radial support force tester for testing (n=3), the compression distance is 50% of the stent diameter, and the maximum radial support force value is obtained. The specifications of the measured stents are 25mm in diameter and 14mm in height, which are the same as the commercially available competitive products. The test samples are samples of comparative example 2, example 1, example 4, and their samples extracted in simulated body fluid-PBS for 1d, 2d, 1 month, 2 months, and 4 months (n=3). The extraction conditions are the same as the drug release determination. The test results are as follows: Fig. 9 shown.
[0234] from Fig. 9 It can be seen that the supporting force of Examples 1 and 4 is better than that of Comparative Example 2. Examples 1 and 4 were extracted in simulated body fluid for 1 day, 2 days, 1 month, 2 months, and 4 months, and the supporting force of the extracted stents was tested. The change in the supporting force was only 0.1%-0.5%, while the supporting force of Comparative Example 2 was reduced by more than 90% after 3 days of extraction, and the intra-batch error was large.
[0235] 5. Animal Wound Repair Test
[0236] Test method: The coated drug-loaded stents prepared by the commercially available competitor, Example 4, and Example 7-8 were implanted into the left and right maxillary sinuses of beagles. The specifications of the above stents were all 25 mm in diameter and 14 mm in height. Before implantation, the beagles were first injected with intramuscular injection of ceftiofur sodium and subcutaneous injection of meloxicam for surgical anti-inflammatory and surgical analgesia, respectively; then atomization anesthesia was performed; then, with the help of endoscopy, nasal polyp forceps, bent needles, etc. were used to treat the wound of the maxillary sinus (using a bent 1 mL syringe needle, the maxillary sinus mucosa was longitudinally scraped on all four sides of the inner wall of the maxillary sinus, and after conventional compression and hemostasis, the stent was implanted into the maxillary sinus using a delivery device); after implantation, the beagles were injected with intramuscular injection of ceftiofur sodium for postoperative anti-inflammatory, once a day, for 5 consecutive days; subcutaneous injection of meloxicam for postoperative analgesia, once a day; and the nasal cavity was cleaned with physiological seawater every day.
[0237] One month and four months after stent implantation, the recovery of the wound surface was observed by nasal endoscopy. Fig. 9 This is the wound condition of the marketed competitor product 1 month after implantation. Fig.10 The wound surface condition of the coated drug-eluting stent of Example 4 after implantation for one month.
[0238] Depend on Fig. 9 It can be seen that one month after the biodegradable bare stent of a competitor on the market was implanted into the maxillary sinus of the beagle dog, coral-like polyps had appeared on the wound surface, the sinus opening was blocked, and the recovery was poor; Fig.10It can be seen that although the stent of Example 4 has been implanted in the maxillary sinus of the beagle for 4 months, the stent can still be easily pulled out, and the wound surface after being pulled out is intact and has no bleeding, and there are no abnormal lesions such as coral polyps, which is no different from the nasal cavity of a healthy dog. By comparing their positions before and after the implantation of the stent, it can also be seen that the stent of Example 4 did not shift after implantation; when cleaning the nasal cavity of the beagle, it was found that the stent of Example 4 had very few foreign bodies, while the foreign bodies of the commercially available competitive bare stents were many, most of which were hung on the stent fragments. The reason for these phenomena is that the commercially available competitive bare stents are made of degradable materials, which are difficult to maintain long-term support and cannot guarantee the drainage of the sinus cavity after surgery. At the same time, its mesh structure has a low drug loading, and the area of contact with the wound surface is also very small, the anti-inflammatory effect is weak, and coral polyps are prone to appear; while the coated drug-loaded stent has a large contact area with the wound surface, and the long-term stable support structure makes the drug release long-term and stable, and has a good anti-inflammatory and anti-adhesion effect. In addition, the presence of the tissue guidance layer restores the wound surface to its original state, which plays a good role in guiding tissue regeneration. The postoperative recovery effect of the drug-eluting stent with a guiding layer is significantly better than that of the biodegradable bare stent.
[0239] 6. HE staining:
[0240] The coated drug-eluting stents prepared in Example 4 and Comparative Example 3 were implanted into the maxillary sinus of beagle dogs, and the specific surgical steps were the same as the above-mentioned animal wound repair experiment.
[0241] One month after implantation, the stent was removed, the mucosal part in contact with the stent was removed, fixed with formaldehyde solution, dehydrated and transparentized, and then immersed in dye solution for HE staining. After staining, it was observed under a microscope and photographed. Fig.11 and Fig.12 As shown, Fig.11 This is a HE staining image of the mucosal tissue contacting the stent after the coated drug-eluting stent of Example 4 was implanted in a beagle dog. Fig.12 This is a HE staining image of the mucosal tissue contacting the stent after the stent of Comparative Example 3 was implanted into a beagle dog. Fig.11 and Fig.12 It can be seen that after the coated drug-eluting stent of Example 4 with a guide layer was implanted in the maxillary sinus of a beagle dog for one month, the mucosal tissue began to undergo normal epithelialization, while after the stent of Comparative Example 3 without a guide layer was implanted in the maxillary sinus of a beagle dog for one month, the epithelialization of the mucosal tissue was discontinuous and difficult to undergo normal epithelialization. This result occurs because the guide layer of the present invention presents a skeletal fibrous reticular structure after being washed and degraded by body fluids, and cells can adhere and grow well, and are effectively guided and directed to grow, so that the wound tissue begins to epithelialize smoothly and normally.
[0242] The present invention has been specifically described above in conjunction with specific embodiments. These specific embodiments are only used for illustration and cannot be used to limit the scope of protection of the present invention. Those skilled in the art may make various modifications, changes or substitutions to the present invention without departing from the essence and scope of the present invention. Therefore, various equivalent changes made according to the present invention still belong to the scope covered by the present invention.
Claims
1. A nasal film-covered drug-eluting stent, characterized in that: include: Stent graft; A drug coating, the drug coating is covered on the surface of the coated stent, the drug coating includes a therapeutic drug and a carrier thereof, wherein the carrier includes a first polymer and a second polymer, the first polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and its derivatives; the second polymer is selected from one or more of the following materials: glycolide-lactide copolymer (PLGA), polylactic acid (PLA), polycaprolactone (PCL), polyglycolic acid (PGA), chitosan, polyamino acid (PAA), polyethylene glycol (PEG), polyorthoester (POE) and its derivatives.
2. The nasal film-coated drug-eluting stent according to claim 1, characterized in that: The mass ratio of the first polymer to the second polymer is (1:9) to (7:3).
3. The nasal film-coated drug-eluting stent according to claim 1, characterized in that: The stent graft comprises: at least one bare stent, each bare stent having a first surface and a second surface opposite thereto, and made of a non-degradable material; A first coating layer covers and adheres to a first surface of the bare stent; A second covering layer, covering and adhering to the second surface of the bare stent; The materials of the first coating layer and the second coating layer include non-degradable materials or degradable materials with a degradation period of more than 4 months.
4. The nasal film-coated drug-eluting stent according to claim 3, characterized in that: The material of at least one bare stent includes one or more of the following materials: nickel-titanium alloy, stainless steel, polyurethane, silicone; the material of the first coating layer and the second coating layer includes one or more of the following materials: expanded polytetrafluoroethylene membrane (ePTFE), silicone membrane, polyurethane membrane (TPU), polyester membrane, polyurethane membrane, gelatin membrane, polycaprolactone, lactic acid-glycolic acid copolymer, polylactic acid.
5. The nasal film-covered drug-eluting stent according to claim 3, characterized in that: The pore size and thickness of the first coating layer and the second coating layer are designed such that: the pore size of the first coating layer is larger than the pore size of the second coating layer, and the thickness of the first coating layer is smaller than the thickness of the second coating layer; The pore size and thickness of the first coating layer and the second coating layer are designed as follows: the membrane pore size of the second coating layer is 0.1-10 μm, and the thickness of the second coating layer is 30-100 μm.
6. The nasal film-coated drug-eluting stent according to claim 3, characterized in that: It includes at least two bare stents, which are arranged at intervals from each other.
7. The nasal film-coated drug-eluting stent according to claim 1, characterized in that: The stent also includes a guide layer, which covers the surface of the drug coating, and the guide layer includes a third polymer and a fourth polymer; the third polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof; the fourth polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof.
8. A method for preparing a nasal film-coated drug-eluting stent, characterized in that: The following steps are involved: (a) forming a stent graft having a first surface and a second surface opposite thereto; (b) forming a drug coating on the first surface and the second surface of the stent graft; The drug coating is formed by a drug coating solution, which includes a therapeutic drug and a carrier thereof, wherein the carrier includes a first polymer and a second polymer, the first polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof; the second polymer is selected from one or more of the following materials: glycolide-lactide copolymer (PLGA), polylactic acid (PLA), polycaprolactone (PCL), polyglycolic acid (PGA), chitosan, polyamino acid (PAA), polyethylene glycol (PEG), polyorthoester (POE) and derivatives thereof.
9. The preparation method according to claim 8, characterized in that: In step (b), the drug coating solution is prepared in the following order: the therapeutic drug is firstly mixed with one of the first polymer and the second polymer to form a mixed solution, and then the mixed solution is mixed with the other of the first polymer and the second polymer to form a drug coating solution; or, The first polymer and the second polymer form a mixed solution which is then mixed with the therapeutic drug to form a drug coating solution.
10. The preparation method according to claim 9, characterized in that: In the drug coating solution, the mass ratio of the first polymer to the second polymer is (1:9) to (7:3).
11. The preparation method according to claim 8, characterized in that: In step (a), forming the stent graft comprises the following steps: Providing at least one bare stent, each bare stent having a first surface and a second surface opposite thereto, and being made of a non-degradable material; Covering the first surface and the second surface of the bare stent with a first coating layer and a second coating layer respectively, and adhering the coating layers to the first surface and the second surface of the bare stent by melt bonding, so as to form a coated stent; The first coating layer and the second coating layer are made of non-degradable materials or degradable materials with a degradation period of more than 4 months.
12. The preparation method according to claim 11, characterized in that: The materials of the first coating layer and the second coating layer include one or more of the following materials: expanded polytetrafluoroethylene film (ePTFE), silicone film, polyurethane film (TPU), polyester film, polyurethane film, gelatin film, polycaprolactone, lactic acid-hydroxyacetic acid copolymer, polylactic acid; the adhesive material used for adhesion includes one or more of the following materials: polyurethane (TPU), fluorinated ethylene propylene (FEP), perfluoroalkyl (PFA), polyvinylidene fluoride (PVDF).
13. The preparation method according to any one of claims 8 to 12, characterized in that: The invention also includes step (c): forming a guide layer on the drug coating, wherein the guide layer is formed by a guide layer solution, and the guide layer solution includes a third polymer and a fourth polymer; wherein the third polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof; and the fourth polymer is selected from one or more of the following materials: polyurethane (TPU), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyurethane (PU), polyacrylamide (PAM) and derivatives thereof; and wherein the mass ratio of the third polymer to the fourth polymer is 90:10 to 10:
90.
14. The preparation method according to claim 13, characterized in that: In step (b), the drug coating solution is applied to the surface of the stent graft by ultrasonic spraying; In step (c), the guiding layer solution is coated on the surface of the drug coating by ultrasonic spraying process.
Citation Information
Patent Citations
Drag sustained release stent
CN109394399A
A sinus stent and its preparation method
CN111529150B
Drug-loaded degradable 3D printing paranasal sinus stent and preparation method thereof
CN112932737A
A sinus stent and delivery system
CN117137700B
Full-degradable paranasal sinus drug stent and manufacturing method thereof
CN117179977A